A rare case of septic cavernous sinus thrombosis as a complication of sphenoid sinusitis - Ming-Chun Chen; Yu-Huai Ho; Pau-Nyen Chong; Jui-Hsia Chen (Tzu Chi Medical Journal)
Isolated sphenoid sinusitis is a rare disorder and may present with severe complications due to its proximity to the orbital and intracranial areas. We report a 13-year-old boy hospitalized for septic shock with fever of unknown origin. Facial palsy was later noted. Brain magnetic resonance imaging showed a sphenoid mass and right cavernous sinus and internal jugular vein thrombosis. Biopsy revealed chronic rhinosinusitis. Complete recovery followed by an incision/drainage procedure and antibiotic treatment. Acute sphenoid sinusitis should be included in the differential diagnosis of septic manifestations mimicking central nervous system infection or cranial nerve palsy.